Utility of Genetic Testing in Patients with Transthyretin Amyloid Cardiomyopathy: A Brief Review - Ana-Maria Merino-Merino; Jorge Labrador-Gomez; Ester Sanchez-Corral; Pedro-David Delgado-Lopez; Jose-Angel Perez-Rivera (Biomedicines, 2023)
Transthyretin amyloid cardiomyopathy (ATTR-CM) is an increasingly diagnosed condition. Although wild-type transthyretin amyloidosis (ATTRwt) is the most common ATTR-CM, hereditary transthyretin amyloidosis (ATTRv) may also occur. Currently, genetic testing for transthyretin pathogenic variants is recommended for patients with a confirmed clinical diagnosis of ATTR-CM. In fact, confirmation of this autosomal dominant pathogenic variant prompts genetic counselling and allows early identification of affected relatives. Additionally, in the presence of an ATTR-CM-associated polyneuropathy, specific drugs targeting transthyretin can be used. In this paper, we review the utility of genetic testing for the detection of pathogenic variants among patients harboring ATTR-CM and its impact on the natural history of the disease.